Initiating and Assessing an e-Nudging Model for Higher Education in Saudi Arabia - Alotaibi, Salihah (Curtin University, 2021)
This research designed an e-nudge model for Saudi Universities to encourage students to make better education decisions. A mixed-method approach was conducted comprising an online survey and interviews to assess the model critically. The outcomes are a model with key factors for effective implementation and practical recommendations. This research addresses the challenges associated with students’ educational decisions. The research contributes by integrating Human Computer Interaction (HCI) and usability as key factors in the model.